Dari Kualitas Teknis ke Persepsi Publik: Bagaimana Kinerja Infrastruktur Jalan Membentuk Kepuasan Pengguna - Suni Attabik; Jojok Widodo Soetjipto; Indra Nurtjahyaningtyas (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2026)
Road infrastructure performance has traditionally been assessed using engineering indicators; however, evidence linking technical performance with perceived safety and user satisfaction remains limited. This study examines the relationships among Road Infrastructure Technical Quality, Road User Safety, and Road User Satisfaction in Banyuwangi Regency, Indonesia. Technical quality was evaluated through pavement and drainage conditions, while user perceptions were collected using structured questionnaires. Data from 98 road users across 19 representative road sections were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that Technical Quality significantly improves Road User Safety (β = 0.812), which, in turn, significantly influences Road User Satisfaction (β = 0.809). Mediation analysis revealed a significant indirect effect of Technical Quality on Satisfaction through Safety (β = 0.657; 95% CI = 0.512–0.803; VAF = 100%), indicating full mediation. The model explains 66.0% of the variance in user satisfaction. These findings suggest that improvements in pavement and drainage conditions enhance user satisfaction primarily by increasing perceived safety. This study provides empirical evidence that integrates engineering performance assessment with user-perception analysis, supporting performance-based infrastructure asset management and road investment prioritization. Keywords: Road infrastructure quality; User safety perception; User satisfaction; Engineering performance indicators; PLS-SEM.